Experimental investigation of the mechanical properties of ZAR-345 cold-formed steel at elevated temperatures - Landesmann,Alexandre (2014)
Considering the technical-scientific advances of recent years in the steel construction industry, there is a strong trend for the increasing use of cold-formed steel members in civil construction, due to several advantages such as cost and versatility of fabrication and erection. However, there is need for further study concerning the behavior of this type of steel when subjected to fire conditions. This work deals with the experimental characterization of cold-formed steel at high temperatures. It is recognized that the reduction factors of the mechanical properties applicable to hot-rolled steel members do not remain valid for cold-formed ones. In the case of the European Code, cold-formed members are treated in the same way of hot-rolled or welded thin-walled sections (i.e., class 4), the only differences in relation to the other (class 1, 2 or 3) consisting (i) the definition of the yield strength and (ii) the corresponding reduction factors (shown in Table E.1 of appendix E of EC3-1.2:2005). In this context, coupon tensile tests were carried out according to recommendations proposed by AS 2291:2007 standard for ZAR-345 (ABNT NBR 7008-1:2012) (or ASTM A653-2011- SS50(340)C1, equivalent). The variation of the constitutive relations (stress-strain-temperature curves) was measured for different uniform temperatures, ranging from 20 ºC (ambient) to 100-200-300-400-500-600 ºC. The obtained experimental results indicate a clear distinction with the models proposed by other authors as well as specifications of EC3-1.2:2005.